PRODUCTIVITY AND PROFITABILITY IN PRODUCTION OF CABBAGE - Pesevski, Mile; Ralević, Nebojsa; Živković, Dragić; Rajić, Zoran; Jelić, Sreten (Economics of Agriculture, 2010)
The authors perform an analysis of economic indicators in the production of cabbage in the Republic of Macedonia, based on statistics (2005- 2009) and data from directly interviewed thirty family holdings. In doing so, they found that cabbage in this country is produced on average area of 3,947 hectares. Total production, with an average yield of 22,342 kg/ha, is 88,182 tones in average, which is 11.4% of the total production of horticultural products. Production of cabbage is mainly concentrated in three statistical regions, as follows: 37.43% in the Southeast region, 12.54% in Pelagonia region and 11.15% in Polog region of the total area in the country. Because of that, surveys are carried out in these three regions. Labor productivity varies between 30.0 kg/h in the Southeast and 34.9 kg/h in Polog region and inside the region 26.7 to 39.2 kg/h. Although average yields at the surveyed producers are largest in Polog region (on average 39,980 kg/ha), the efficiency of invested assets is lowest. The profit is 211.6 EUR/ha in average. This is why they sell the entire production on the wholesale market where the purchase price is lowest. In contrast, highest profit (on average 1,389.4 EUR/ha) accomplish the producers from Pelagonia region because they produce with lowest unit costs and sell the products with highest price, compared to other producers.